(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the population density indicators of the administrative districts of the Republic of Uzbekistan. The analyses were first analyzed by the traditional (gross) method, and then by the newly developed land capacity method. The results of both analyses are compared and differences are identified. The shortcomings of the methodology for creating population density indicators, which are maintained in current statistical departments and administrative departments, are explained. The article uses methods of system analysis, comparative geographical research.